Ecopedagogy-Based Teaching Materials Development to Train Social Skills and Sustainability Awareness of Grade IV Elementary Students - Sriwianti; Agustin, Mubiar (International Conference on Elementary Education, 2022)
Humans with all their activities in meeting the needs of life make the condition of the earth increasingly fragile. This condition is exacerbated by destructive behavior and lack of human consciousness which is essentially as a multidimensional being has a reciprocal relationship with nature. This has an impact on the erosion of environmentally friendly life which is part of ecopedagogy at various levels of life. Based on early studies the lack of availability of teaching materials books specifically to train social skills and sustainability awareness of elementary school students. Teaching materials are an important component in learning used by teachers in the process of teaching and learning activities or as a source of learning that can help students in learning. The method used in this study is a literature review that tries to delve deeper into the importance of developing ecopedagogy-based teaching materials to train the social skills and sustainability awareness of elementary school students supported by the results of previous research. The results show that efforts are needed to develop teaching materials to fit the needs and be able to train social skills and sustainability awareness of elementary school 4th grade students.